HOSPITAL MANAGEMENT RELATED TO PATIENT LOYALTY VIEWING FROM SERVICE QUALITY, SATISFACTION, IMAGE AND VALUE - Suyanto Ph.D (Universal Journal, 2021)
Health development in Indonesia aims, among others, at making quality, fair and proportionate health services accessible to the Indonesian. Various development efforts have been implemented to realize such ideal covering infrastructure, medical personnel quality, access, health service process and professional attitude presented by hospital. This research objectively aims at analyzing patient loyalty from the perspectives of service quality, image, value and satisfaction of patients of hospitals in Bandung City. 296 in-patients of hospitals type B in Bandung City chosen by accidental random sampling were taken as the sample of this research. This research employs SEM statistically processed using AMOS as its analysis test tool. The results of this research state that from 10 Hypotheses,